Peer support and mental resilience among high school students - Dewi, Rofida Kumara; Sutejo, Sutejo; Rahayu, Prastiwi Puji (JOURNAL OF Mental Health Concerns, 2026)
Background: Resilience is an individual's ability to survive, adapt, and bounce back in the face of stress or problems. In adolescence, especially high school students, resilience is greatly influenced by the social environment, one of which is peer social support. Positive support from peers can help students manage academic and social stress more adaptively. Purpose: To determine the relationship between peer social support and resilience in high school students. Method: Quantitative design with a descriptive correlational approach and a cross-sectional design. The population of this study was high school students, with samples selected using a purposive sampling technique. The research instruments were peer social support questionnaires and RISC 25 CD questionnaires. Data analysis was carried out univariately and bivariately using the Spearman Rho test. Results: Most students have moderate peer social support and high resilience. The results of the correlation test showed a P Value = 0.00 (P <0.05) with an r-count value = 0.496 which indicates sufficient correlation strength. Conclusion: There is a significant relationship between peer social support and resilience in high school students. Keywords: Adolescents; Peer Social Support; Resilience.